Mapping students learning needs through design thinking to support critical thinking in mathematics - Nabila Zulfaniar, Eva; Purwosetiyono, FX Didik; Buchori, Achmad (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aims to investigate how the Design Thinking framework can be systematically utilized to map junior secondary students’ learning needs in mathematics to support the development of critical thinking skills. Method: An exploratory qualitative design was employed, applying the empathize, define, and ideate stages of the Design Thinking process. The participants consisted of 80 students from Grades VII–IX and 7 mathematics teachers from three junior secondary schools in Pemalang Regency, Indonesia. Data were collected through expert-validated questionnaires, classroom observations, and semi-structured interviews. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing, supported by triangulation to ensure credibility. To reinforce the proposed instructional solutions, a quantitative meta-analytic synthesis of five relevant empirical studies was conducted using JASP software to estimate pooled effect sizes. Findings: The results indicate a substantial discrepancy between conventional teacher-centered instruction and students’ need for interactive, visual, and problem-oriented learning experiences. The ideation stage produced three key solutions: booklet-based materials, Creative Problem Solving (CPS) activities, and gamified digital tools such as QuizWhizzer. The meta-analytic findings demonstrated a moderate and statistically significant pooled effect size (ES = 0.740, p < 0.05), supporting the potential effectiveness of these approaches in fostering critical thinking. Significance: This study offers a structured framework for integrating Design Thinking into mathematics learning needs analysis and provides evidence-based guidance for designing innovation-oriented instructional practices.